Tectonic role of margin‐parallel and margin‐transverse faults during oblique subduction in the Southern Volcanic Zone of the Andes: Insights from Boundary Element Modeling. Issue 9 (5th September 2016) - Stanton‐Yonge, A.; Griffith, W. A.; Cembrano, J.; St. Julien, R.; Iturrieta, P.
Abstract: Obliquely convergent subduction margins develop trench‐parallel faults shaping the regional architecture of orogenic belts and partitioning intraplate deformation. However, transverse faults also are common along most orogenic belts and have been largely neglected in slip partitioning analysis. Here we constrain the sense of slip and slip rates of differently oriented faults to assess whether and how transverse faults accommodate plate‐margin slip arising from oblique subduction. We implement a forward 3‐D boundary element method model of subduction at the Chilean margin evaluating the elastic response of intra‐arc faults during different stages of the Andean subduction seismic cycle (SSC). Our model results show that the margin‐parallel, NNE striking Liquiñe‐Ofqui Fault System accommodates dextral‐reverse slip during the interseismic period of the SSC, with oblique slip rates ranging between 1 and 7 mm/yr. NW striking faults exhibit sinistral‐reverse slip during the interseismic phase of the SSC, displaying a maximum oblique slip of 1.4 mm/yr. ENE striking faults display dextral strike slip, with a slip rate of 0.85 mm/yr. During the SSC coseismic phase, all modeled faults switch their kinematics: NE striking fault become sinistral, whereas NW striking faults are normal dextral. Because coseismic tensile stress changes on NW faults reach 0.6 MPa at 10–15 km depth, it is likely that they can serve as transient magma pathways during this phase of the SSC. Our model challenges the existing paradigm wherein only margin‐parallel faults account for slip partitioning: transverse faults are also capable of accommodating a significant amount of plate‐boundary slip arising from oblique convergence. Key Points: Transverse‐to‐the‐orogen faults may also participate in slip partitioning resulting from oblique subduction We implement a forward 3‐D model of Andean subduction to simulate interseismic and coseismic deformation We constrain kinematics, slip rate, and seismic hazard associated with differently oriented regional faults